Mechanisms and Insights for the Development of Heart Failure Associated with Cancer Therapy - Claire Fraley; Sarah A. Milgrom; Lavanya Kondapalli; Matthew R. G. Taylor; Luisa Mestroni; Shelley D. Miyamoto (MDPI AG, 2021)
Cardiotoxicity is a well-recognized late effect among childhood cancer survivors. With various pediatric cancers becoming increasingly curable, it is imperative to understand the disease burdens that survivors may face in the future. In order to prevent or mitigate cardiovascular complications, we must first understand the mechanistic underpinnings. This review will examine the underlying mechanisms of cardiotoxicity that arise from traditional antineoplastic chemotherapies, radiation therapy, hematopoietic stem cell transplantation, as well as newer cellular therapies and targeted cancer therapies. We will then propose areas for prevention, primarily drawing from the anthracycline-induced cardiotoxicity literature. Finally, we will explore the role of human induced pluripotent stem cell cardiomyocytes and genetics in advancing the field of cardio-oncology.